Bacterial meningitis in Nottingham. - Ispahani, P. (Cambridge University Press, 1983)
Records of 171 cases of bacterial meningitis admitted to Nottingham hospitals from January 1974 to June 1980 were reviewed. The distribution of organisms producing meningitis and the factors influencing mortality in different age groups were assessed. Neisseria meningitidis, Haemophilus influenzae and Streptococcus pneumoniae accounted for 69% of all proven cases. The overall mortality was 26% being lowest in patients with meningococcal meningitis (0%) and highest in those with pneumococcal meningitis (53%). The following factors were associated with a poor prognosis: age more than 40 years, or less than 2 months; state of consciousness on admission; high CSF protein concentration; and a positive blood culture. There was no evidence that antibiotic therapy prior to admission affected prognosis. Although many laboratory findings were altered by prior treatment with antibiotics, this did not prevent the establishment of a diagnosis in the individual patient.